AGR Challenge for Bharti Airtel and Vodafone Idea. Issue 2 (June 2021) - Anand, Manoj; Singh, Jagandeep
In 2018, India had 1.2 billion subscribers, and it was the second largest telecommunications market in the world. The industry had witnessed the emergence, ascendency, and dominance of private sector players during the last two decades. The telecom sector was characterized by a growing wireless user base and Internet subscriber base. The dwindling average revenue per user (ARPU) in the mobile telephony segment and the declining average cost to subscriber per GB of data were manifestations of the intense rivalry in the sector which had led to price wars among incumbent players. The Supreme Court of India's judgement on Adjusted Gross Revenue (AGR) in October 2019 obligated the industry players to pay ₹1, 470 billion as payment towards their licence fee and spectrum usage charges. Vodafone Idea and Bharti Airtel, two leading players, collectively owed 60% of the aforementioned liability. Declining revenue had already squeezed the profitability and liquidity of these companies. The AGR liability augmented their challenges.